(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
This research was conducted to identify the effects of different doses of auxin on the cutting of Mulberry (Morus alba). The study was conducted in Syangja district from April 2022 to June 2022. Stem cuttings of the plant were subjected to different treatments; IBA concentration (Control, 1000 ppm, 2000 ppm, 3000 ppm, and 4000 ppm). The experiment was carried out in a Randomization Complete Block Design (RCBD) and replicated thrice. The physiology of mulberry is highly affected by auxin, a rooting hormone. In the case of different IBA concentrations, the maximum rooting percentage (81.33%) was found in cuttings which were treated with a 4000 ppm concentration of auxin. Similarly, cuttings treated with 2000 ppm auxin develop an abundance of leaves (11), primary roots (9), and secondary roots (12). But in the case of root length (22.33 cm), the highest was found in cuttings which were treated with a 4000 ppm concentration of IBA. IBA was found to be most effective at 4000 ppm for best rooting and good root growth, and at 2000 ppm for healthy leaf growth and to enhance the number of primary and secondary roots in Mulberry. Vol. 9, No. 3, December 2022: 253-257